2021
DOI: 10.1021/acssensors.0c01701
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nano/Micro-Islands Overcome the Molecularly Imprinted Polymer Limitations to Achieve Ultrasensitive Protein Detection

Abstract: Here, we report on an electrochemical biosensor based on core–shell structure of gold nano/micro-islands (NMIs) and electropolymerized imprinted ortho-phenylenediamine (o-PD) for detection of heart-fatty acid binding protein (H-FABP). The shape and distribution of NMIs (the core) were tuned by controlled electrodeposition of gold on a thin layer of electrochemically reduced graphene oxide (ERGO). NMIs feature a large active surface area to achieve a low detection limit (2.29 fg mL–1, a sensitivity of 1.34 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Last, as noted above, the detection of H-FABP is limited and generally based upon immunoassays, with very limited reports using MIPs [ 208 ]. For example, Sanati et al [ 208 ] reported the development of a MIP based biosensor, based upon ITO modified electrochemically reduced graphene oxide (ERGO).…”
Section: Current Electrochemical/electroanalytical Approaches To Dete...mentioning
confidence: 99%
See 2 more Smart Citations
“…Last, as noted above, the detection of H-FABP is limited and generally based upon immunoassays, with very limited reports using MIPs [ 208 ]. For example, Sanati et al [ 208 ] reported the development of a MIP based biosensor, based upon ITO modified electrochemically reduced graphene oxide (ERGO).…”
Section: Current Electrochemical/electroanalytical Approaches To Dete...mentioning
confidence: 99%
“…Last, as noted above, the detection of H-FABP is limited and generally based upon immunoassays, with very limited reports using MIPs [ 208 ]. For example, Sanati et al [ 208 ] reported the development of a MIP based biosensor, based upon ITO modified electrochemically reduced graphene oxide (ERGO). These were modified with highly active surface area core–shelled gold nano/micro-islands (NMIs) via electrodeposition, which allows their size to be tuneable via controlling the electrodeposition process.…”
Section: Current Electrochemical/electroanalytical Approaches To Dete...mentioning
confidence: 99%
See 1 more Smart Citation
“…130 At present, the detection of H-FABP is mostly focused on combining antibody capture probe and nanomaterials, while the research of MIPs-ECS is less. 131,132 Sanati et al 133 developed an electrochemical biosensor with a core–shell structure of nano/micro-islands (NMIS) and MIPs prepared by electrodeposition method to detect H-FABP in biological fluids. The steps of the MIPs biosensor fabrication and H-FABP detection are shown in Fig.…”
Section: Application Of Mmips-cs In Biomarker Detectionmentioning
confidence: 99%
“…The selection of appropriate biorecognition elements significantly affects the overall analytical cost and lifetime performance of biosensors. 21,22 Biorecognition elements, including antibodies, DNA-aptamers, recognition peptides and some synthetic molecules, have been employed to detect cancer cells using cytosensors. These biorecognition elements exhibit a high affinity to antigens on the cancer cells' surface, thereby making specific bonding with cancer cells.…”
Section: Biorecognition Elements In the Detection Of Ctcsmentioning
confidence: 99%